ANALISIS STRATEGI PENGEMBANGAN WAKAF PRODUKTIF DI PESANTREN - Gelar Permana, Didik; Ibdalsyah; Erismen Armen, Rio (Universitas Ibn Khaldun Bogor, 2021)
The purpose of this study was to analyze the implementation of productive waqf in Al-Ma'tuq Islamic Boarding School and Islamic Mabda by using the Waqf Core Principles (WCP), also to analyze the strengths, weaknesses, potentials and obstacles of waqf management and to analyze the ideal strategy for the development of productive waqf in pesantren. The research method used is a qualitative method with a field study approach. The techniques used in data collection are observation, interviews, and documentation studies. Analysis of the data used is descriptive comparative analysis. Keywords: waqf core principles (WPC); productive waqf.